Managing professional development in education : issues in policy and practice - Glover, Derek (Kogan Page, 1996)
This work evaluates and attempts to produce a model for effective professional development. It contrasts the work in Britain with that in other countries, with case studies and exercises to illustrate points, highlighting good practice.